Maternal urinary manganese and risk of low birth weight: a case-control study - Wei Xia; Yanqiu Zhou; Tongzhang Zheng; Bin Zhang; Bryan A. Bassig; Yuanyuan Li; John Pierce Wise; Aifen Zhou; Yanjian Wan; Youjie Wang; Chao Xiong; Jinzhu Zhao; et al. (BMC, 2016)
Abstract Background Manganese (Mn) is an essential element for humans, but exposure to high levels has been associated with adverse developmental outcomes. Early epidemiological studies evaluating the effect of Mn on fetal growth are inconsistent. Methods We investigated the association between maternal urinary Mn during pregnancy and the risk of low birth weight (LBW). Mn concentrations in maternal urine samples collected before delivery were measured in 816 subjects (204 LBW cases and 612 matched controls) recruited between 2012 and 2014 in Hubei Province, China. Results The median Mn concentration in maternal urine was 0.69 μg/g creatinine. Compared to the medium tertile of Mn levels, an increased risk of LBW was observed for the lowest tertile (≤0.30 μg/g creatinine) [adjusted odds ratio (OR) = 1.28; 95 % confidence interval (CI) = 0.67, 2.45], and a significantly increased risk of LBW was observed for the highest tertile (≥1.16 μg/g creatinine) [adjusted OR = 2.04; 95 % CI = 1.12, 3.72]. A curvilinear relationship between maternal urinary Mn and risk of LBW was observed, showing that the concentration at 0.43 μg/g creatinine was the point of inflection. Similar associations were observed among the mothers with female infants and among the younger mothers < 28 years old. However, among the mothers with male infants or the older mothers ≥ 28 years old, only higher levels of Mn were positively associated with LBW. Conclusions Lower or higher levels of maternal urinary Mn are associated with LBW, though only the association of LBW risk and higher levels of Mn was statistically significant. The findings also show that the associations may vary by maternal age and infant sex, but require confirmation in other populations.